2019
DOI: 10.1039/c9ra07415e
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine ion induced phase evolution of tin-based perovskite thin films: structure and properties

Abstract: Fluorine dopant inhibited the oxidation process in CsSnI3−xFx films with high carrier concentration, low resistivity and wide light absorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…It should be noted that SnF 2 doping can inhibit the phase transition of CsSnI 3 at room temperature, and the retarded phase transition is due to the stronger bond between F and Sn than that between I and Sn. [60] These results imply that CsSnI 3 is very sensitive to air, thermal, and organic solvents. Therefore, exploration of strategies, that can stabilize the photovoltaic phase of CsSnI 3 at room temperature (i. e., B-γ phase), is of great importance to realize PSCs with high PCE and device stability.…”
Section: Crystallographic Propertymentioning
confidence: 93%
“…It should be noted that SnF 2 doping can inhibit the phase transition of CsSnI 3 at room temperature, and the retarded phase transition is due to the stronger bond between F and Sn than that between I and Sn. [60] These results imply that CsSnI 3 is very sensitive to air, thermal, and organic solvents. Therefore, exploration of strategies, that can stabilize the photovoltaic phase of CsSnI 3 at room temperature (i. e., B-γ phase), is of great importance to realize PSCs with high PCE and device stability.…”
Section: Crystallographic Propertymentioning
confidence: 93%
“…Therefore, fluoride complex was introduced as additive to improve the stability of Sn‐based PVK. Wu et al [108] . demonstrated that F ion dopant inhibits the oxidation process, and slows down the phase transformation of CsSnI 3 into Cs 2 SnI 6 .…”
Section: Other Halides and Pseudo‐halides Additives For Pvk Filmsmentioning
confidence: 99%
“…A high carrier mobility of ∼ 10 2 to 10 3 cm 2 V −1 s −1 for Sn‐based perovskites was demonstrated by Stoumpos and coworkers, [ 7,14 ] As candidate materials for PVs, Sn‐based perovskites retain superior optoelectronic properties such as long diffusion lengths. It was reported by Wu and coworkers that melt‐synthesized CsSnI 3 ingots which contained high‐quality single crystals exhibited diffusion lengths reaching 1 µm with bulk carrier lifetimes approaching 6.6 ns and doping concentrations of ∼4.5 × 10 17 cm −3,[ 15,16 ] On the other hand, Sn‐based perovskites are direct‐bandgap semiconductors, viz. the valence band maximum (VBM) and the conduction band minimum (CBM) lie at the same point in reciprocal space, and possess narrower bandgaps compared with their Pb analogues.…”
Section: Chemical Structurementioning
confidence: 99%